2002
DOI: 10.1111/j.1471-3802.2002.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Adapting instruction to address individual and group educational needs in maths

Abstract: This study, combining classwide curriculum‐based measurement and peer‐mediated instruction, used a single‐subject research design to address the effectiveness of two grouping adaptation strategies (heterogeneous small‐groups versus peer tutoring) to accommodate individual and group differences in learning. Academic performance in the domains of number and arithmetic skills of 19 low, average, and high achieving first‐grade linguistic minority pupils was measured by recording scores over 12 weeks and across mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Other research on human tutoring strategies tends to focus on such things as grouping students and peer tutoring (e.g., Cardona, 2002) and are not explicit about the specific strategies used in those settings. In a recent literature review that had a focus on human tutoring strategies, Naidu (2006) found that many human tutors have students solve problems while addressing errors as they arise and confirming steps when correct.…”
Section: Discussionmentioning
confidence: 99%
“…Other research on human tutoring strategies tends to focus on such things as grouping students and peer tutoring (e.g., Cardona, 2002) and are not explicit about the specific strategies used in those settings. In a recent literature review that had a focus on human tutoring strategies, Naidu (2006) found that many human tutors have students solve problems while addressing errors as they arise and confirming steps when correct.…”
Section: Discussionmentioning
confidence: 99%
“…A theoretical body regarding curricular adaptations was developed (González Manjón, 1993;Garrido Landívar, 1998;García Vidal, 1999), but little is known about the practices teachers actually carry out in their classrooms. An exception can be found in Cardona's studies about teachers' use of general and specific instructional adaptations (Cardona, 2002), and their perceptions about these strategies (Cardona, 2003a(Cardona, , 2003b. Findings from these studies indicate a moderate acceptance of instructional adaptations, but we lack knowledge as to whether these strategies differ as a function of grade level taught, training, and the availability of resources and support.…”
Section: Introductionmentioning
confidence: 99%